2010
DOI: 10.1093/eurheartj/ehq258
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular manifestations in men and women carrying a FBN1 mutation

Abstract: The CV risk remains important in patients with an FBN1 gene mutation and is present throughout life, justifying regular aortic monitoring. Aortic dilatation or dissection should always trigger suspicion of a genetic background leading to thorough examination for extra-aortic features and comprehensive pedigree investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
90
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 46 publications
10
90
0
2
Order By: Relevance
“…1 We also observed that patients with aortic dissection had a higher frequency of a protein-truncating or -splicing variant (86%) as compared with patients with prophylactic aortic surgery (69%), although this observation was not statistically significant. In addition, we noted a trend in association between genotype and age at aortic surgery, dissection, or both.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…1 We also observed that patients with aortic dissection had a higher frequency of a protein-truncating or -splicing variant (86%) as compared with patients with prophylactic aortic surgery (69%), although this observation was not statistically significant. In addition, we noted a trend in association between genotype and age at aortic surgery, dissection, or both.…”
Section: Discussionmentioning
confidence: 63%
“…Détaint et al 1 previously reported on cardiovascular manifestations in 1,013 probands with pathogenic FBN1 mutations. They observed that the probability of an aortic event before the age of 30 years in their cohort was 16% in men and 11% in women; before the age of 40 years this probability was ~40-45% in men and 25% in women.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations